10
1.) jika g(x) = ( 5 -3x ) maka g"(2) adalah ..

2.) diketahui f(x) = ( x - a )² + ( a + 1 ) x - 14. jika nilai f ' (1) = -1 maka nilai f(a) = .....

3.) diketahui f(x) = (2x - 4) (3x + 3) , f ' (x) adalah turunan pertama dari f(x). nilai f ' (-2) adalah ....

1

Jawabanmu

2014-05-11T21:38:55+07:00
F(x) = (2x-4)(3x+3)
 F’(x) = 1 (2x-4)1-1 2(3x+3) +1 (3x+3)1-1 3(2x-4)
= (2x-4)0 2(3x+3) +(3x+3)0 3(2x-4)
 = (1) 2(3x+3) +(1) 3(2x-4)
 =6x+6+6x-12
=12x-6
=2x-1

f(-2) = 2(-2) -1
=-4-1
= -5
Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus
Komentar sudah dihapus